Epêntese vocálica em encontros consonantais por falantes brasileiros de inglês como língua estrangeira - Nascimento, Geisibel Cristina Andrade [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This Master's thesis aims to analyze the insertion of epenthetic vowel in consonant clusters in the pronunciation of the English language by Brazilian learners. The aspect analyzed in this research refers to the difficulty that English language students have to produce the consonant sounds, especially those which are not part of the phonological system of their mother language, Brazilian Portuguese, or that are not used similarly. The corpus was composed by words, which contain, in onset and/or coda position, segments or sequences of segments that are different from those found in Brazilian Portuguese in order to check how English learners would produce them. We selected 46 words from Longman Communication 3000, a list of the 3,000 most repeated words in English. We have asked 30 English students, from different levels of proficiency (basic, intermediate and advanced) to read the selected words aloud. The reading was recorded and, from the recordings, phonetic transcriptions of the informants' pronunciation were done for each word. From these transcriptions, it was possible to make the analysis about the production of each informant. A statistical analysis was done to verify the frequency of the insertion of the epenthetic vowel in order to correct the structures of the English language, which are not familiar to the learner, i.e., those ones that are not part of their mother language. After that, the data were analysed considering the Optimality Theory to see how the constraints behave in a foreign language learning. We concluded that the insertion of the epenthetic vowel is a strategy that is frequently used in the pronunciation of English words that has segments and/or sequences of segments in onset or coda position which are different from those that are found in Brazilian Portuguese. However, the epenthesis is not the only one. The palatalization of /t/ and /d/ and the aspiration of /p/, /t/ and /k/ were frequently used too ...

Esta dissertação de mestrado tem por objetivo analisar a inserção de vogal epentética em encontros consonantais na pronúncia da língua inglesa por aprendizes brasileiros. A questão trabalhada nesta pesquisa se refere à dificuldade que os alunos de língua inglesa apresentam em produzir os sons consonantais, especialmente aqueles que não fazem parte do sistema fonológico de sua língua materna, o português brasileiro, ou que não são usados da mesma forma. Como corpus, foram utilizadas palavras que possuem, em posição de onset e/ou coda, segmentos ou sequências de segmentos diferentes daqueles encontrados no português brasileiro com o intuito de verificar como os aprendizes de inglês os produziriam. Foram selecionadas 46 palavras que foram retiradas do Longman Comunication 3000, uma lista das 3.000 palavras mais utilizadas em inglês. Pediu-se a 30 informantes, estudantes de inglês de diferentes níveis de proficiência (básico, intermediário e avançado), que lessem as palavras selecionadas em voz alta. A leitura foi gravada, e a partir das gravações foram feitas transcrições fonéticas da realização dos informantes para cada palavra. A partir dessas transcrições, foi possível fazer uma análise a respeito das produções de cada informante. Foi feita uma análise estatística para verificar a frequência da utilização da inserção de vogal epentética na correção das estruturas da língua inglesa não familiares ao aprendiz, ou seja, diferentes daquelas com as quais ele já está familiarizado, que fazem parte da sua língua materna. Em seguida, os dados foram analisados considerando a Teoria da Otimalidade para verificar como as restrições se comportam na aprendizagem de uma língua estrangeira. Constatou-se que a inserção da vogal epentética é uma estratégia frequentemente utilizada na pronúncia de palavras do inglês que possuem segmentos e/ou sequências de segmentos em onset e/ou coda diferentes...
Keywords: Língua inglesa; Fonética; Fonologia; Pronuncia; Teoria da otimalidade (Linguística); English language